PELESTARIAN NILAI-NILAI QUR’ANI DALAM RITUAL MAJELIS TAUSHIYAH DAN DZIKIR DI PP. ASWAJA LINTANG SONGO : (STUDI LIVING QUR’AN) - Nurul Istiqomah (Institut Agama Islam Negeri (IAIN) Keiri, 2017)
This paper appointed the Taushiyah Assembly and dhikr, if it is associated with the Geertz trichotomy is a ritual associated with santri. In this assembly Mr. Heri gives taushiyah from Islamic sources such as the Qur’an, Hadith, and Ulama’s books. Tradition is very thick content with the santri. The interesting thing to be lifted from this assembly is that although the taushiyah and dhikr assemblies are santri traditions, but the jama’ah who follow this assembly come from the priyayi and abangan elements. Priyayi elements such as Geertz’s trichotomy in this assembly can be represented by government officials, military personnel and village apparatus. The abangan element in this assembly can be represented from the community around Pager Gunung who often do ritual Slametan. These three different elements have different goals and captures in following the Taushiyah and dhikr assemblies. The author will show an example of the three elements of santri, priyayi and abangan in following the taushiyah and dhikr majlis. Taushiyah activities and dhikr are activities in which contain several aspects that can be examined, we can see from what they read, the tolerance of study community, and the Kyai’s strategy that made this study lasting by incorporating Qur’anic values. The Qur’anic values given by Kyai to the community are derived from the Qur’anic verses that derive the essence of his lesson to be applied in the daily life of the community. Qur’anic values are meant lessons that can be taken for daily life derived from the content of verses in the Qur’an. In this study, the author will discuss about the stability that exists in this taushiyah and dhikr majlis and their relationships with the preservation of Qur’anic values in it. Then also the preservation of Qur’anic values when applied in the life jama’ah. To analyze the stability of taushiyah and dhikr assemblies, the author used the theory of functional structuralism initiated by Talcott Parson. The focus of the study was on the four functions of value that are adaptation, purpose, integration, and latent situation.